Upaya Pelestarian Musik Talempong Pacik di Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan - Jeni Martha Wuri; Wimbrayardi Wimbrayardi; Marzam Marzam (SENDRATASIK UNP, 2015)
Abtract This research was conducted to reveal and describe the efforts done to preserve Talempong Pacik traditional art in Koto XI Tarusan Kabupaten Pesisir Selatan. The object of the research was Talempong Pacik traditional art in Koto XI Tarusan. Talempong Pacik was chosen as the object of the research as this traditional art is almost exinct. This was a qualitatif research. The data were gathered through interview, obsevation and documentation. The instrument of the research was the reseacher herself as the key instrument. The data were selected, presented and verified. The result of the research indicated that there were some efforts were done by the people in Koto XI Tarusan to preserve Talempong Pacik. The efforts were done by establishing an art group, recruiting new members, and carring out regular training once a week in Koto XI Tarusan Kabupaten Pesisir Selatan. Keywords: Pelestarian, Talempong Pacik.